A elaboração da memória em Rithy Panh - Tomyo Costa Ito (2021)
This research studies the filmography of Cambodian filmmaker Rithy Panh, in his effort in the elaboration of the traumatic past of his country. We sought to analyze four of his documentaries that address the genocide perpetrated by the Khmer Rouge regime in Cambodia, from 1975 to 1979. To understand the filmmaker's work of memory, the thesis was based on studies of the philosophy of history (Walter Benjamin) and psychoanalysis (Freud and Lacan). The film analysis investigated the peculiar relationship between who films and who is filmed, the testimony narratives and the resignification of archival images. Four modalities of cinematographic elaboration of Cambodian collective memory were identified: the nomination in Bophana, a Cambodian Tragedy (1996), the encounter in S-21: The Khmer Rouge Killing machine (2002), the confrontation in Duch, Master of the Forges of Hell (2011) and the remembrance in The Missing Picture (2013).